Digital Children's Literature Storynory.Com Impact to English Department UNP's Listening Anxiety of EFL College Students - Ahlal Ahwida; Leni Marlina (Journal of English Language Teaching, 2023)
Digital children's literature is a listening and reading medium that can be accessed not only by children but also adults. The aims of this study to determine whether using digital children's literature Storynory.com has a good impact on reducing students' listening anxiety. A collection of digital children's literature stories from Storynory.com is used in this research. A quantitative technique and a quasi-experimental research design are used in this research. This research has a population of EFL students, especially students enrolled in the (UNP) for the 2022/2023 academic year. Data is collected by using pre-test which is has 20 question, daily treatment which is contain 15 stories (1 day one stories), and post-test which is has 20 questions. Data was analyzed by SPSS 20. Based on the study's findings, digital children's literature Storynory.com help students feel less anxious about listening. This proves that the utilization of children's digital literature is a successful medium that has a positive effect and can be a solution in reducing listening anxiety of EFL college students in the English Department, UNP.